2015
DOI: 10.1152/ajpendo.00527.2014
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone increases nitric oxide synthesis in human vascular endothelial cells through activation of membrane progesterone receptor-α

Abstract: Pang Y, Dong J, Thomas P. Progesterone increases nitric oxide synthesis in human vascular endothelial cells through activation of membrane progesterone receptor-␣. Am J Physiol Endocrinol Metab 308: E899 -E911, 2015. First published March 24, 2015; doi:10.1152/ajpendo.00527.2014.-Progesterone exerts beneficial effects on the human cardiovascular system by inducing rapid increases in nitric oxide (NO) production in vascular endothelial cells, but the receptors mediating these nongenomic progesterone actions re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
49
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 75 publications
(117 reference statements)
5
49
0
Order By: Relevance
“…12 Progesterone is known to stimulate nitric oxide synthesis via transcriptional and non-transcriptional pathways in human endothelial cells. 1316 Nitric oxide expression generally increases during pregnancy and decreases before parturition, 17 and nitric oxide is known to regulate vasodilation, smooth muscle relaxation, and the inflammatory response during pregnancy. However, myometrial relaxation occurs in a cGMP-independent manner.…”
Section: Commentmentioning
confidence: 99%
“…12 Progesterone is known to stimulate nitric oxide synthesis via transcriptional and non-transcriptional pathways in human endothelial cells. 1316 Nitric oxide expression generally increases during pregnancy and decreases before parturition, 17 and nitric oxide is known to regulate vasodilation, smooth muscle relaxation, and the inflammatory response during pregnancy. However, myometrial relaxation occurs in a cGMP-independent manner.…”
Section: Commentmentioning
confidence: 99%
“…These actions are relatively unaffected by inhibitors of transcription, as mimicked by steroids coupled to nonpermeant cell membrane molecules and persist in cells that do not express the classic genomic progesterone receptor . The mPRs belong to the progestin and adipoQ receptor (PAQR) family and were first identified in teleost fish, although it was later discovered that 5 subtypes (mPRα, mPRβ, mPRγ, mPRδ and mPRε) are found in tissues of several mammalian species, including humans . These receptors contain 7 transmembrane domains, display high‐affinity progesterone binding and rapidly activate G proteins during their downstream signalling pathways following progestin binding .…”
Section: Introductionmentioning
confidence: 99%
“…However, some found that physiologically high progesterone levels are associated with increased congestive heart failure prevalence [37], while the first clues of its role in energy metabolism only emerged more recently, i.e. mediating its effects via the progesterone receptor-α to subsequently activate PI3-K/AKT-1 and MAPK in addition to increased endothelial nitric oxide (eNOS) activity and NO production [38, 39]. …”
Section: Introductionmentioning
confidence: 99%